'I use the words you taught me': Beckett and Political Repetition. Issue 1 (April 2021) - Davies, William
Abstract : Repetition is a key element of Samuel Beckett's writing. Phrases, themes, even whole texts repeat themselves throughout his oeuvre. This article situates this habit of repetition within two contexts: the tumultuous politics of the 1930s and 1940s through which Beckett lived, in which the repetitions of propaganda came to define political existence; and the 2020 COVID-19 pandemic, in which nationwide lockdowns brought new forms of repetition to citizens around the world as societies strove to respond to the virus spread. In doing so, this article uses Beckett's responses to his historical moment to think through the political rhetoric of lockdown and national solidarity which emerged during the pandemic, particularly in the UK.